Analisis Desain Komunikasi Visual sebagai Subjek Pelestarian Seni Budaya dan Kearifan Lokal Minangkabau - Vernanda Em Afdhal; M. Sayuti (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
This research stems from the analysis and review process of the field of Visual Communication Design (VCD) as one of the disciplines that contribute to the preservation of Minangkabau culture and local wisdom. From several research findings, it is evident that VCD can be considered as an academic discipline, and more narrowly, visual communication design media can be employed as a subject in preserving Minangkabau culture and local wisdom. One of the objectives of this research is to underscore that the field of visual communication design, as a subject, can be utilized to promote efforts to preserve and enhance the existence of this discipline in conserving the culture. The research methodology adopted for this study is qualitative (literature review and content analysis). Data were collected through the process of analyzing and reviewing books, journals, articles, and works produced through visual communication media. The research results manifest in descriptive statements that emphasize visual communication design's potential as a medium for preserving Minangkabau culture and local wisdom. Furthermore, this research can be used as a reference and can contribute to the development of the curriculum in the case study area, namely the Visual Communication Design program located in West Sumatra